Seed priming effects on seed quality, stand establishment and yield of direct seeded crops: A review (Bangladesh Journal of Nuclear Agriculture, 2025)
Seed priming can be employed to reduce the duration of germination, to synchronize germination, to improve germination rate and to improve field stand of low-quality seeds. Seed priming helps to develop the embryo before germination with increasing α-amylase activity, and the content of fructose and glucose, and with reducing sucrose content. Total sugar content of primed seed was higher than non-primed seeds. Germination of soybean seed lot stored for 16 months improved by priming treatment from 10.0 to 50.5%. Priming treatment of soybean seeds stored more than 12 months also reduced T50 by 0.3 to 1.0 days. Rapid and uniform emergence increases the stand establishment which influences better growth tend to better yield. Priming influences the emergence of seedling and stand establishment and it has a subsequence impact on yield and yield attributes. In general, plant population at harvest was closely related with emergence percentage of seed and plant population was positively correlated with seed yield.Bangladesh J. Nuclear Agric, 39(2): 111-122, 2025